A multiscale and multivariate analysis of precipitation and streamflow variability in relation to ENSO, NAO and PDO - Nalley, D.; Adamowski, J.; Biswas, A.; Gharabaghi, B.; Hu, W. (Journal of hydrology (Amsterdam), 2019)
•Multiscale and multivariate analyses of ENSO, NAO and PDO on precipitation and flow.•Wavelet-based models were used to perform multiscale and multivariate analyses.•Positive and negative phases caused drier and wetter conditions, respectively.•Annual periodicity characterized precipitation and streamflow variability.•Three-factor combinations were needed to explain the precipitation and flow variability. A number of past studies have investigated the influence of various teleconnections – such as El Niño-Southern Oscillation (ENSO), the North Atlantic Oscillation (NAO) and the Pacific Decadal Oscillation (PDO) – on precipitation and streamflow. These studies, however, have not focused on analyzing the combined influence of the different phases of these teleconnections and the simultaneous influence of these teleconnections at differing time-frequency scales. The present study addresses this issue by exploring the use of wavelet-based methods in combination with non-parametric approaches to analyze individual and combined influences involving ENSO, NAO, and PDO on monthly precipitation and streamflow data from watersheds in Alberta, Ontario, and Newfoundland, in Canada. This study is the first time that multiscale and multivariate analyses of ENSO, NAO, and PDO, along with their different phases, are used to explain the variability of streamflow and precipitation in a watershed. Generally, the positive and negative phases (particularly of ENSO and NAO) were respectively associated with lower and higher precipitation/streamflow, while the neutral phase showed similar behavior to that of the negative phase. The results of the bivariate and multivariate wavelet coherences revealed that there were consistent increases in the average wavelet coherence (AWC) and the percentage of significant coherence (PoSP) for all watersheds, from using only one factor to two and three teleconnection factors. The ranges of AWC for one, two and three factors were 0.31–0.40, 0.56–0.66, and 0.77–0.81, respectively. The ranges of PoSP for one, two and three factors were 3.54–14.3, 28.38–47.29, and 69.28–76.71, respectively. This implies that three-factor combinations (ENSO-NAO-PDO) were needed to explain the variability of precipitation and streamflow in all watersheds.